Sustainable Tourism Destination Development Based on Gstc Criteria: a Swot Analysis Study in Ubud, Bali Tourism Area - MAHOTTAMA, I Made Tegar Upadana; DEWI, Ni Putu Novita Candra; WIDANA, I Gede Arya; DESTHARETA, I Made Dwika (Journal Management and Hospitality, 2024)
Ubud, Bali, is known as one of the leading tourist destinations in Indonesia that implements the principle of sustainability in its development. In addition to its natural beauty, which includes terraced rice fields and tropical forests, Ubud is also the centre of Balinese art, culture, and spirituality. This uniqueness is reinforced by the active involvement of local communities in tourism management and a commitment to preserving culture and the environment. The principles of sustainable tourism in Ubud align with the local philosophy of Tri Hita Karana and can be evaluated against international standards, such as those set by the Global Sustainable Tourism Council (GSTC). GSTC has developed criteria that cover four main pillars: destination management, socio-economic impact, cultural preservation, and environmental protection. This article aims to analyze tourism management in Ubud based on the GSTC criteria, utilizing a SWOT analysis approach. Through this analysis, the strengths, weaknesses, opportunities, and threats faced by Ubud in implementing sustainable tourism can be identified, as well as strategic recommendations for future destination development.